2014
DOI: 10.3389/fnagi.2014.00134
|View full text |Cite
|
Sign up to set email alerts
|

Human longevity is associated with regular sleep patterns, maintenance of slow wave sleep, and favorable lipid profile

Abstract: Some individuals are able to successfully reach very old ages, reflecting higher adaptation against age-associated effects. Sleep is one of the processes deeply affected by aging; however few studies evaluating sleep in long-lived individuals (aged over 85) have been reported to date. The aim of this study was to characterize the sleep patterns and biochemical profile of oldest old individuals (N = 10, age 85–105 years old) and compare them to young adults (N = 15, age 20–30 years old) and older adults (N = 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
45
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 51 publications
1
45
1
Order By: Relevance
“…Sleep appears to be fundamental to animal life, yet little is known about how sleep has evolved throughout the animal kingdom. In diverse animal taxa, poor sleep can have detrimental effects on development (Roffwarg et al, 1966;Mirmiran et al, 1983;Kayser et al, 2014), cognitive abilities (Scullin and Bliwise, 2015) and life span (Mazzotti et al, 2014), and it is now appreciated that normal sleep is fundamental to healthy physiology and bodily function (Shaw et al, 2002;Cappuccio et al, 2010;Arble et al, 2015). While the function of sleep remains unknown, studies have identified relationships between sleep and anatomical, physiological or ecological traits (Lesku et al, 2006;Capellini et al, 2008;McNamara et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Sleep appears to be fundamental to animal life, yet little is known about how sleep has evolved throughout the animal kingdom. In diverse animal taxa, poor sleep can have detrimental effects on development (Roffwarg et al, 1966;Mirmiran et al, 1983;Kayser et al, 2014), cognitive abilities (Scullin and Bliwise, 2015) and life span (Mazzotti et al, 2014), and it is now appreciated that normal sleep is fundamental to healthy physiology and bodily function (Shaw et al, 2002;Cappuccio et al, 2010;Arble et al, 2015). While the function of sleep remains unknown, studies have identified relationships between sleep and anatomical, physiological or ecological traits (Lesku et al, 2006;Capellini et al, 2008;McNamara et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…HDL has several atheroprotective functions and has been recognized as a longevity marker . HDL has chief roles in plasma cholesterol esterification and reverse cholesterol transport and additional anti‐inflammatory, antioxidant, anticoagulant, antithrombotic, vasodilatory, and antiapoptotic properties.…”
mentioning
confidence: 99%
“…The relation between sleep and neurodegenerative diseases is bidirectional [40]. Neurodegeneration is accompanied by sleep difficulties due to reduction of amplitude and phase changes of circadian rhythms such as that of melatonin secretion, as well as the disturbing influences of neurodegenerative processes on sleep.…”
Section: Sleep Disturbances In Admentioning
confidence: 99%
“…Neurodegeneration is accompanied by sleep difficulties due to reduction of amplitude and phase changes of circadian rhythms such as that of melatonin secretion, as well as the disturbing influences of neurodegenerative processes on sleep. Conversely, inadequate sleep, in terms of both duration and quality, increases the neurodegenerative process and aggravates the underlying clinical picture [40]. …”
Section: Sleep Disturbances In Admentioning
confidence: 99%